Sistem Pendukung Keputusan Pemilihan Karyawan Teladan Pada PT. XYZ Dengan Metode Simple Multi Attribute Rating Technique - Fajriyah, Nurul; Setiawan, Wawan; Duha, Tobias (Jurnal Informatika, 2024)
In daily life activities, every human being will be faced with various problems that will require them to make the right decisions in order to solve these problems. So to make important decisions, more careful, unhurried and mature considerations will be needed. Decision making is also carried out by organizations and companies, for example at PT. To make it easier to select appropriate exemplary employees, based on the company's needs, a decision support system using the SMART method is used. The SMART method is more widely used in calculating alternatives and ranking, because it is simple in responding to researchers' needs in making decisions and analyzing responses. The author collected the data needed to be processed in selecting exemplary employees. This stage of the data collection process was obtained by the author from observation, interviews and literature studies. Criteria for evaluating exemplary employees include attendance, discipline, responsibility, work targets and length of service. After evaluating alternative employees, an exemplary employee with the highest score was obtained.